DANGERS ON THE ROAD FAILURES IN 'DRIVING ADVICE IN NEUROLOGICAL DISORDERS'. Issue 12 (15th November 2016) - Yoga, Bindu; Randall, Marc
Abstract : Objective: Recent news events have highlighted that patients may not be aware of the DVLA guidelines for driving. There may be complex reasons why advice is not followed but it should at least be given. How often neurologists consider driving at time of assessment in the neurology clinic was of interest. Methodology: A prospective review of 102 new patient notes from randomly selected neurology clinics over 3 months was completed. A survey assessing knowledge of neurologists and trainees of commonly encountered neurological disorders was performed in tandem. Results: 43.1% (45/102) of patients had driving status recorded. 48.9% (22/45) were car drivers. 15.7% (16/102) of all patients were documented to have received driving advice. Correct driving advice was given in 11.76% (12/102), 1.96% (2/102) was unknown as exact advice was not documented. The documentation of driving advice was noted in 36.7% (37/102) of cases where as in 63.7% (65/102) cases there was no documentation. Conclusions: Significant numbers of neurological presentations don't affect driving but even frequent migraines or dizzy turns should trigger an enquiry to assess risk to patients and others. Appropriate advice can include "no need to stop driving" but a decision should be documented. Strategies to improve assessment need developing.